Mechanisms of ciliary targeting: entering importins and Rabs - Lu, Lei (2018)
Primary cilium is a rod-like plasma membrane protrusion that plays important roles in sensing the cellular environment and initiating corresponding signaling pathways. The sensory functions of the cilium critically depend on the unique enrichment of ciliary residents, which is maintained by the ciliary diffusion barrier. It is still unclear how ciliary cargoes specifically enter the diffusion barrier and accumulate within the cilium. In this review, the organization and trafficking mechanism of the cilium are compared to those of the nucleus, which are much better understood at the moment. Though the cilium differs significantly from the nucleus in terms of molecular and cellular functions, analogous themes and principles in the membrane organization and cargo trafficking are notable between them. Therefore, knowledge in the nuclear trafficking can likely shed light on our understanding of the ciliary trafficking. Here, with a focus on membrane cargoes in mammalian cells, we briefly review various ciliary trafficking pathways from the Golgi to the periciliary membrane. Models for the subsequent import translocation across the diffusion barrier and the enrichment of cargoes within the ciliary membrane are discussed in detail. Based on recent discoveries, we propose a Rab–importin-based model in an attempt to accommodate various observations on ciliary targeting.